Evaluacion de dos biofertilizantes (bocashi líquido, te dé estiércol) en tres sistemas de cultivo en Lechuga (lactuca sativa. l) Alangasi - Pichincha 2021. - Ruiz Villacis, Cristina Roció (2021)
The objective of the research was to validate the effectiveness of two biofertilizers (liquid bocashi and manure tea) in three cultivation systems (hydroponics, semi-hydroponics and soil), applied to lettuce (Lactuca sativa L), which allowed the analysis and comparison of the variables evaluated; 5 nutritive solutions were prepared as treatments, 2% enriched manure tea, 2% unenriched manure tea, 5% enriched liquid bocashi, 5% unenriched liquid bocashi and a chemical nutritive solution, in order to compare the yields in green mass, dry mass, root density, the percentage incidence of pests and diseases, and the behavior of pH and EC were monitored during the whole crop cycle; In hydroponics, the recirculation method was used with 5 pool pumps; in semi-hydroponics, recycled material was used with a rice husk substrate; and in soil, a cultivation bed was used. An experimental design of completely randomized blocks (DBCA) was applied. For each of the treatments, a water volume of 80 liters of water was used; variable 1 is green mass yield (MV), variable 2 is dry mass (DM), variable 3 is root density (RD), significance tests were performed for each treatment and where there was a significant difference, the Tukey test was performed; the best interactions in this research were for the variable MV green mass and DM dry mass was chemical solution plus soil system (QSU) with 317.43 g green mass MV occupying the first category in commercial weight and 2.91g dry mass DM; for the variable DR root density was chemical solution in hydroponic system (HQ) with 7.09 g/ml with a root with a greater number of main and secondary roots and more ramifications; For the variable pH and electrical conductivity EC was the chemical solution with a range of pH 6.5 to 7.5 and EC 990 to 1180 ds/m which helped to a better absorption of nutrients to the crop and for the variable % of incidence was hydroponics (H) and semi-hydroponics (S) with a range of 0 to 5 % of incidence which favors to obtain a clean and better quality product.